[View of Cal Poly campus] (1954)
View of main campus, Dexter Library, Administration Building, Poly Ninos (Vetville), Poly Vue Trailers, North Mountain, construction of Science Building - looking east at Poly "P". View of O'Neill Green and Poly Grove. View of the P.